2019
DOI: 10.3390/pharmaceutics11090465
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of the Solvent-Assisted Active Loading Technology (SALT) for Liposomal Loading of Poorly Water-Soluble Compounds

Abstract: A large proportion of pharmaceutical compounds exhibit poor water solubility, impacting their delivery. These compounds can be passively encapsulated in the lipid bilayer of liposomes to improve their water solubility, but the loading capacity and stability are poor, leading to burst drug leakage. The solvent-assisted active loading technology (SALT) was developed to promote active loading of poorly soluble drugs in the liposomal core to improve the encapsulation efficiency and formulation stability. By adding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 49 publications
0
55
0
Order By: Relevance
“…This would be attributed to the small amount of DMSO and Cu 2+ . It was reported that the addition of DMSO could improve the solubility of the insoluble drug and enhance liposomal membrane permeability 18 , 28 . On the other hand, once the PSD was loaded into the intraliposomal aqueous phase, it would bind with Cu 2+ to form a water-insoluble complex Cu 2+ –PSD, thus, in turn, would facilitate to the process of drug loading.…”
Section: Resultsmentioning
confidence: 99%
“…This would be attributed to the small amount of DMSO and Cu 2+ . It was reported that the addition of DMSO could improve the solubility of the insoluble drug and enhance liposomal membrane permeability 18 , 28 . On the other hand, once the PSD was loaded into the intraliposomal aqueous phase, it would bind with Cu 2+ to form a water-insoluble complex Cu 2+ –PSD, thus, in turn, would facilitate to the process of drug loading.…”
Section: Resultsmentioning
confidence: 99%
“…However, the stresses imposed during the freeze-drying process might lead to the leakage of the encapsulated drugs (Ingvarsson et al, 2011). The drug leakage depends on the liposome composition and on the nature of drug (Pauli et al, 2019). Thus, it is imperative to study the freezedrying process on drug leakages, and evaluate their influence on the final liposomal formulations behavior.…”
Section: Influence Of the Freeze-drying On Drug Leakage From Liposomesmentioning
confidence: 99%
“…Generally, this method gives low encapsulation efficiency mostly for hydrophobic compound. While active methods, such as pH gradient or solvent-assisted active loading technology, are used for different types of molecules and consist in the preformation of liposomes containing a transmembrane gradient [15]. Surface functionalization of liposomes is an alternative method to conjugate peptides to liposomes and enhances cellular uptake, prevents lysosomal degradation and improves the stability of nanoparticles [16].…”
Section: Liposomementioning
confidence: 99%